Occupational sitting time and subsequent risk of cancer: The Japan Public Health Center‐based Prospective Study. Issue 3 (5th February 2020) - Ihira, Hikaru; Sawada, Norie; Yamaji, Taiki; Goto, Atsushi; Shimazu, Taichi; Kikuchi, Hiroyuki; Inoue, Shigeru; Inoue, Manami; Iwasaki, Motoki; Tsugane, Shoichiro; ,
Abstract: Although occupational sitting time has been associated with adverse health outcomes and mortality, the association with cancer incidence remains unknown. This study investigated the association between occupational sitting time and risk of total and site‐specific cancer in a Japanese population. We evaluated 33 307 participants aged 50‐79 years who responded to a questionnaire in 2000‐2003 in the Japan Public Health Center‐based Prospective Study and were followed until 2013. Participants were grouped by sitting time at work. Hazard ratio (HR) and 95% confidence interval (CI) of cancer incidence were calculated with adjustment for potential confounders including moderate‐to‐vigorous physical activity. During 10.2 years of follow‐up, 3807 newly diagnosed cases of cancer were identified. Occupational sitting time was marginally associated with total cancer, with multivariable HRs for the ≥7 h/d vs 1 to <3 h/d category of 1.12 (95% CI, 0.99‐1.26; P for trend = .071) in men, but not women. Among findings for cancers at specific sites, long occupational sitting time was associated with increased risk of pancreas cancer, with multivariable HRs for the ≥7 h/d vs 1 to <3 h/d category of 2.25 (95% CI, 1.17‐4.34; P for trend = .021) in men, and lung cancer, with multivariable HRs for the ≥7 h/d vs 1 to <3 h/d category of 2.80 (95% CI, 1.33‐5.90; P for trend = .013) in women. Extended sitting time at work was associated with an increased risk of pancreas cancer in men and lung cancer in women. Abstract : The purpose of this study was to evaluate the associations between occupational sitting time and risk of total and site‐specific cancer in a Japanese population. Extended sitting time at work was associated with an increased risk of pancreas cancer in men and lung cancer in women.